Risk Management Based on Islamic Boarding School - Ekaningsih, Lely Ana Ferawati; Salim, Ubud; Djumahir, Djumahir; Indrawati, Nur Khusniyah; Djakfar, Muhammad (IQTISHODUNA: Jurnal Ekonomi Islam, 2022)
Uncertainty is often associated with risk, in Islamic economics the concept of uncertainty becomes one of the important pillars in the Islamic risk management process. Nothing in this life is free from risks and facts in every organization and its activities. The purpose of this research is to reveal and explain in depth the implementation of Islamic boarding school risk management.The paradigm used is post-positivistic. This type of research uses case studies. The key informant is the manager of the pesantren. Data analysis was carried out by an interactive analysis of the model from Miles and Huberman. The application of risk management at the Manba'ul Ulum Islamic boarding school in Banyuwangi Regency from the results of the study stated that it was very beneficial/positive, as evidenced by the increase in the number of students studying at the pesantren after experiencing the pandemic period from 2019. Islamic values ​​frame Islamic boarding school risk management activities as a source of inspiration and aspirations. Has been applied by the predecessors and is a character that shapes the santri so that they are not shaken under any conditions, besides that it is also sourced from the Islamic values ​​​​of the Qur'an and hadith as principles, then the educational curriculum is sourced from the book of ridhotun nashihin or akhlaq.